A 12-year-old boy presented with fever and left-sided upper abdominal pain (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below:A 12-year-old boy of non-consanguineous parents presented with the history of fever and left sided upper abdominal pain for 1 month. His fever was high grade, intermittent, associated with chills and rigor. The abdominal pain was dull aching in nature without any radiation, aggravating or relieving factors. His bowel habit was normal. The child had no history of jaundice, cough, respiratory distress, burning sensation during micturition, earache, skin infection, contact with tubercular patient, blood transfusion or parenteral medica-tion. On examination, she was fretful, febrile, mode-rately pale, and anicteric. Tachycardia was present. Per abdominal examination revealed tenderness at the left hypochondriac region.